Determinants of social media’s use in consumer behaviour: an international comparison - Bartosik-Purgat, Małgorzata; Filimon, Nela; Hinner, Michael (Economics and Business Review, 2017)
This research focuses on the impact of social media (SM) on their users’ behaviour vis-a-vis their decision to purchase goods and services online as well as their attitudes towards these media. The theoretical framework was grounded in the literature of consumers’ behaviour and their interaction with the digital media with a special focus on individual socio-demographics (age and gender). The literature overview allowed the construction of the research hypotheses taking into account the personal traits and the social media usage in terms of consumer activities. The empirical testing of the hypotheses was performed with quantitative methods of analysis applied to a dataset of SM users from six different countries (Poland, China, Spain, Germany, Turkey and US). Findings have shown that SM preferences and their frequency of use have different impacts on consumer behaviour both depending on individual characteristics. Some implications for business managers and marketeers are discussed.